Brainstem cavernous malformations: Natural history versus surgical management. (October 2016) - Walcott, Brian P.; Choudhri, Omar; Lawton, Michael T.
Highlights: Hemorrhagic brainstem cavernous malformations have an estimated 5-year recurrent hemorrhage risk of 30.8%. Hemorrhagic brainstem cavernomas have an estimated 5-year recurrent hemorrhage or a new neurological deficit of 50.7%. In the UCSF series, 14% of patients had a persistent neurological deficit as a result of surgery for brainstem cavernomas. Abstract: While brainstem cavernous malformations were once considered inoperable, improvements in patient selection, surgical exposures, intraoperative MRI-guidance, MR tractography, and neurophysiologic monitoring have resulted in good outcomes in the majority of operated patients. In a consecutive series of 104 patients with brainstem cavernous malformations, only 14% of patients experienced cranial nerve or motor dysfunction that was worse at late follow-up, relative to their preoperative condition. Outcomes were predicted by several factors, including larger lesion size, lesions that crossed the midline, the presence of a developmental venous anomaly, older age, and greater time interval from lesion hemorrhage to surgery. The 14% of patients who experienced a persistent neurological deficit as a result of surgery, while substantial from any perspective, compares favorably with the risks of observation based on a recent meta-analysis. Curative resection is a safe and effective treatment for brainstem cavernous malformations that will prevent re-hemorrhage in symptomatic patients.